Synthesis of Hematite Pigments (alpha-Fe2O3) by Thermal Transformations of FeOOH - Lilik Miftahul Khoiroh; Diah Mardiana; Akhmad Sabarudin; Bambang Ismuyanto (The Journal of Pure and Applied Chemistry Research, 2013)
Synthesis of iron oxide FeOOH from FeCl3, followed by thermal transformation to form red hematite was conducted. The effect of pH and temperature calcinations was studied. The pigment obtained was analyzed by XRD, color reader and scanning electron microscopy (SEM). The structure crystal of pigment at all variation of pH and calcinations temperature were hematite (a-Fe2O3) with good crystallization and  relatively pure. The color of pigment obtained at pH variation were red with maximum value of L * a* at pH 6 while the mean grain size with minimum coefficient of variation was at pH 8 with mean grain size was 0.17 mm. The maximum of calcinations temperature was at 800oC for 3 hour. The resulting pigment was shaped like a spheres.